Transactions on Engineering Technologies World Congress on Engineering and Computer Science 2017 - Ao, Sio-Iong.; Kim, Haeng Kon.; Amouzegar, Mahyar A.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This volume contains a selection of revised and extended research articles written by prominent researchers participating in a large international conference on Advances in Engineering Technologies and Physical Science which was held in San Francisco, California, USA, October 25-27, 2017. Topics covered include engineering mathematics, electrical engineering, communications systems, computer science, chemical engineering, systems engineering, manufacturing engineering, and industrial applications. With contributions carefully chosen to represent the most cutting-edge research presented during the conference, the book contains some of the state-of-the-art in engineering technologies and the physical sciences and their applications, and serves as a useful reference for researchers and graduate students working in these fields.
1. Classical Young Measures Generated by Oscillating Sequences with Uniform Representation -- 2. Energy Requirements Estimation Models for Iron and Steel Industry Applied to Electric Steelworks -- 3. Technology Landscape 4.0 -- 4. Modeling of Vehicle-Cargo Interaction under Different Environments -- 5. Temperature Optimized Hydrolysis of Acetic Acid Catalyzed Magnesium Hydride for Hydrogen Generation in a Batch Sytem Hydrogen Reactor -- 6. Investigation into the Electrical Conductivity of Carbon Nanosphere-Based Green Nanofluids -- 7. Convective Drying of Ginger Rhizomes -- 8. A Multi-Agent Simutation Study for Congestion Minigation in a University Campus Restaurant -- 9. Dynamic Virtual Bats Algorithm with Probabilistic Selection Restart Technique -- 10. Clustering for binary featured datasets -- 11. Addressing the Challenges of IGBO Computational Morphological Studies Using Frequent Pattern-Based Induction -- 12. Application of Box-Jenkins Model in Predicting Road Traffic Crashes in Nigeria -- 13. Gumbel Distribution: Ordinary Differential Equations -- 14. Half-Normal Distribution: Ordinary Differential Equations -- 15. Sources of Stressors among Physics Education Undergraduates of Chukwuemeka Odumegwu Ojukwu University, Nigeria -- 16. Reactive Power Loss Minimization on an Interconnected Electric Power Network -- 17. Application of Remote Telemetry for Improving Formula SAE Car Performance -- 18. Reliable Energy Generation Using Hybrid System Technology to Improve Standard of Living in the Rural Area -- 19. Android Mobile Malware Classification Using a Tokenization Approach -- 20. Non-Taxonomic Relation Extraction Using Probability Theory -- 21. Insider Threat Veracity Issues -- 22. Why should a Senior Citizen be a Facebook User? -- 23. Archive Browsing System for the Roads with Extremely Delayed Recovery after the 2011 Tohoku Earthquake -- 24. Exponentiated Generalized Exponential Distribution: Ordinary Differential Equations -- 25. Quantifying the Mind: Worry, Tension and Anxiety -- 26. Half-Cauchy and Power Cauchy Distributions: Ordinary Differential Equations -- 27. 3-Papameter Weibull Distribution: Ordinary Differential Equations.
Keywords: Industrial engineering; Production engineering; Computer networks .; Chemistry, Technical; Electrical engineering; Mathematical models; Industrial and Production Engineering; Computer Communication Networks; Industrial Chemistry; Electrical and Electronic Engineering; Mathematical Modeling and Industrial Mathematics